The Tea Planter's Wife - Jefferies, Dinah (Australia Penguin Books, 2015)
Nineteen-year-old Gwendolyn Hooper is newly married to a rich and charming widower, eager to join him on his tea plantation, determined to be the perfect wife and mother. But life in Ceylon is not what Gwen expected. The plantation workers are resentful, the neighbours treacherous. And there are clues to the past - a dusty trunk of dresses, an overgrown gravestone in the grounds - that her husband refuses to discuss. Just as Gwen finds her feet, disaster strikes. She faces a terrible choice, hiding the truth from almost everyone, but a secret this big can't stay buried forever ...
Keywords: Tea plantations -- Sri Lanka -- Secrecy